Drawing Professional Nursing Care: Stories of Memories of the Chilean North from 1952 [Dibujando Cuidados Profesionales de Enfermería: Relatos de Memorias del Norte Chileno a Partir de 1952 - Navarro-Torres, R; Nunez-Carrasco, E; Macias-Inzunza, L (Universidad de Alicante, 2019)
Objective: The objective of this article is to describe the practice of caring for nurses in northern Chile in the context of the new institutional framework of the National Health Service since 1952. Method: A historical analysis was carried out following the methodology provided by Siles (2008), beginning with a historical-practical review of the forms of care of nurses after the creation of the National Health Service. The primary sources are life stories of nurses combined with secondary sources that account for the contextualization of the period of time studied. Results: The following categories were obtained, precedents of the creation of the National Health Service and northern Chile, the science of nursing in daily care, personal knowledge and the health context of the time, ethical tensions in care and the emancipation of nurses. Conclusions: The National Health Service granted a sanitary structure of responsibility of the Chilean State for the health of all its inhabitants. In this scenario, the professional nurses applied the science of nursing in the care of hospitals and communities. Given the social deprivation scenario, the personal knowledge of each one is challenged and in this way empowered them in the development of their professional role. © 2019 Universidad de Alicante. All rights reserved.